Plan de marketing turístico del bosque protector Servio Aguirre de la parroquia Santiago, cantón Loja, provincia de Loja - Piedra Alba, Vanny Lucía (2016)
Currently sustainable tourism and tourism have performed widely aware in Ecuador, this is evidenced by the variety of existing attractions that lend themselves to the development of these types of tourism that has the primary purpose of conserving and preserving ecosystems and flora and wildlife that inhabit them. The diversity that the country has extensive in terms of its flora and fauna is concerned, of the places that make up the territory enhances Loja Province is the same as identified by the culture, music, customs, traditions being part of their identity. In relation to marketing plans and their marketing techniques have positioned nationally and very important locally as a positive determinant of progress in the sectors that apply to present or sell their products and services in the market in which they operate, however these aspects adds the unique attractions that are part of tourism development, you can stand out from the 13 parishes that make up the Canton Loja to rural Parish Santiago and specifically one of its most important natural attractions Protected Forest Servio Aguirre, an attractive tourist features exceptional, but also ideal for research either flora or fauna. The failure to promote Protected Forest Servio Aguirre by the owner is one of the major problems are evident, the internal signaling nonexistent forest, the lack of a tour guide are other factors that influence the sector limited distribution, for which has been raised this thesis topic and this has been important to raise general objective. "Developing a Tourism Marketing Plan to enhance the Protector Forest Servio Aguirre of Santiago Parish, Canton Loja, Loja Province" and three specific objectives are: To make a diagnosis of the current situation of Serbian protected forest of the Parish Santiago Aguirre. Proposal for developing promotional pieces Protected Forest Dr. Serbian Aguirre and Socialization of Marketing Plan proposal to the people involved. To comply with the objectives to different methods were applied fully as scientific, analytical, synthetic and gathering information, conducting surveys, interviews, SWOT and finally the socialization of the proposal developed with key stakeholders in tourism. Through this marketing plan will contribute to tourism development both Protected Forest Servio Aguirre and the Parish Santiago, through the promotion and dissemination of forest with different promotional pieces that are proposed in this thesis proposed the same as highlight its main features and its location in the parish, contributing in this way contribute to tourism development in the forest and therefore the parish Santiago. According to the diagnosis made became evident that the Bosque Protector Serbian Aguirre has a great variety of flora and fauna that can be admired by tourists specialists in this branch; accessibility however shows some difficulty as there is adequate signage for entry also as part of the tourism infrastructure can also be added that the parish no tourist signs to guide tourists to the forest, but may move to the City of Loja head of the canton, with the above we can deduce that the absence of tourist facilities requiring attractive, tourists are likely unaware of the place or show some interest to know that this sexy gorgeous Serbian is the Bosque Protector Aguirre. By the above consideration is the owner and the authorities of the Autonomous Decentralized Parish Santiago, implement and consider this marketing plan. The recommendations that arise to have completed this thesis work are performed based on the result of the implementation of the project such as: The Autonomous Decentralized Government of the Parish Santiago consider this marketing plan for the Protected Forest Servio Aguirre as it will greatly contribute to tourism development not only forest but also to the entire parish owner; To Dr. Cesar Aguirre proprietary of Protected Forest Servio Aguirre, it is recommended to implement tourism infrastructure and internal signage to improve the service that is offered tourists and generate higher revenues, a National University of Loja especially the Engineering Tourism facilitate care professional is recommended to perform the study of implementation of infrastructure and tourist signs for the Forest Servio Aguirre and thus linked more with the community. The culmination of research work contributes to the following conclusions: the problematization of the study area The Protected Forest Servio Aguirre focuses on the lack of a tourism marketing plan that will make known the same and therefore can develop touristically; the completion of the current diagnosis of the Parish Santiago allowed to contribute to the development of this work, by collecting information given in the parish GAD above and forest owner, the same I contribute to the realization of the proposed tourism marketing plan Protected Forest Servio Aguirre; the Protected Forest Servio Aguirre has exceptional attractive features about flora, fauna and landscapes, but even there the road signs to access the site, no internal signaling to facilitate the travel of the same.